PENERAPAN TERAPI MENDONGENG UNTUK MENURUNKAN TINGKAT KECEMASAN PADA ANAK USIA PRASEKOLAH AKIBAT PANDEMI COVID – 19 DI DESA KEBONDALEM KECAMATAN MIJEN KOTA SEMARANG - Ns. Erni Suprapti; Rika Desiana Lydia Sari (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2021)
Preschoolers are children aged three to six years. Covid - 19 is a pandemic that is shaking the world right now. Due to the Covid - 19 pandemic, children cannot play with friends outside the home. Limited play space for children makes it easy for them to feel bored just to stay at home, causing children to become anxious. The purpose of this case study is to apply storytelling play therapy to reduce anxiety levels in preschool-aged children at home due to the covid-19 pandemic. The method of this case study is descriptive. The result of the case study is a decrease in anxiety score in subject I from 45 to 30 and subject II from 51 to 34. The conclusion of this case study shows that storytelling therapy is effective in reducing the anxiety level of preschool children. Suggestions for this case study are expected that parents can apply storytelling to reduce anxiety levels in children at home due to the Covid-19 pandemic.